Influence of cost, quality and organisation of terminal transport and interchanges on the choice of passenger transport mode - Wagon, D. J.; Collins, P. H.; European Conference of Ministers of Transport (Paris : European Conference of Ministers of Transport, 1973)
In this paper, various aspects of the design and location of interchange facilities and feeder services are discussed. The development of mathematical models to predict the effects of such schemes is described and some more general problems of integrating the evaluation of interchange schemes in an urban planning context are also discussed.
At head of title: Economic Research Centre.
ne 08/06/2018
Loans
Keywords: Choice of transportation; Transportation